Factors influencing the quality of life among Indonesian elderly - Bayu Anggileo Pramesona; Surasak Taneepanichskul (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - In spite of being a significant public health concern, quality of life (QoL) amongst elderly in nursing home (NH) settings is rarely analyzed. The purpose of this paper is to examine the level of QoL and factors influencing QoL amongst elderly NH residents in Indonesia. Design/methodology/approach - A survey was conducted amongst 181 elderly at three NHs in three districts in Yogyakarta province, Indonesia. Purposive sampling was used for the study site and sample collection. Face-to-face interviews were performed using the WHO Quality of Life BREF Indonesian version questionnaire to assess elderly QoL. Multivariate linear regression was performed to determine the factors influencing the QoL amongst elderly NH residents. Findings - The response rate was 66.3 percent. A total of 64.1 percent of elderly had a fair level of QoL, whereas 16.6 percent still had a poor level of QoL. A total of 86.7 percent of elderly lived in an NH due to compulsion, and more than half (53.6 percent) perceived inadequacy of care. The QoL was significantly low amongst those who live in NHs due to compulsion, no social support resources, not receiving any kind of support, having three chronic diseases and perceived inadequacy of care (p<0.05). Multivariate analysis revealed that perceived adequacy of care reasons for living in NH was associated with QoL (p<0.001). Originality/value - Perceived adequacy of care and reason for living in an NH were highlighted as predictors of QoL amongst elderly NH residents. Improving adequate healthcare services and developing treatment strategies to enforce the adaptation process is required in order to maintain the QoL in elderly NH residents.